(untitled) (Nordic Journal of African Studies, 2004)
African writers have an enduring propensity for social and political commitment. Their texts mostly reflect and refract the socio-political events in their societies. Initially, African literature was a tool for celebrating the heroic grandeur of the African past; later it was used for anti-colonial struggle. Presently, it is being employed as a veritable weapon for depicting the postcolonial disillusionment in African nations. Therefore, African literature is always chained to the experiences of the peoples of the continent. In this paper, an attempt is made to examine the discourse of postcolonial decadence in contemporary African fiction. One of Meja Mwangi’s novels of postcolonial disillusionment, Kill Me Quick, is used as the case study for the discussion. It is observed that in Mwangi’s prose text, postcolonial pains in African nations are imaginatively captured with apt narrative devices.